2014
DOI: 10.1021/cb500665r
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Glycoside Activities Link Na+/K+ ATPase Ion-Transport to Breast Cancer Cell Migration via Correlative SAR

Abstract: The cardiac glycosides ouabain and digitoxin, established Na+/K+ ATPase inhibitors, were found to inhibit MDA-MB-231 breast cancer cell migration through an unbiased chemical genetics screen for cell motility. The Na+/K+ ATPase acts both as an ion-transporter and as a receptor for cardiac glycosides. To delineate which function is related to breast cancer cell migration, structure–activity relationship (SAR) profiles of cardiac glycosides were established at the cellular (cell migration inhibition), molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 44 publications
3
32
0
2
Order By: Relevance
“…Digitoxin and ouabain blocked HUVEC migration towards different growth factors: VEGF, bFGF, EGF, FBS plus ECGS. Inhibition of cell migration by several cardiac glycosides (ouabain, arenobufagin, bufalin, the cardenolide analogue UNBS1450) has been demonstrated in other cell types, in particular cancer cells, indicating that it might be a common biological effect of this class of drugs (Mijatovic et al , ; Li et al , ; Chueh et al , ; Magpusao et al , ). Interfering with cell migration in the tumour context affects several key processes for cancer development and progression such as angiogenesis, recruitment of inflammatory cells, tumour cells invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Digitoxin and ouabain blocked HUVEC migration towards different growth factors: VEGF, bFGF, EGF, FBS plus ECGS. Inhibition of cell migration by several cardiac glycosides (ouabain, arenobufagin, bufalin, the cardenolide analogue UNBS1450) has been demonstrated in other cell types, in particular cancer cells, indicating that it might be a common biological effect of this class of drugs (Mijatovic et al , ; Li et al , ; Chueh et al , ; Magpusao et al , ). Interfering with cell migration in the tumour context affects several key processes for cancer development and progression such as angiogenesis, recruitment of inflammatory cells, tumour cells invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Na + /K + ‐ATPase is highly expressed in cancer cells. The inhibition of Na + /K + ‐ATPase also exhibits antimigratory activity of breast cancer cells . The SERCA pump is identified as an endoplasmic reticulum (EPR) protein.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of Na + /K + -ATPase also exhibits antimigratory activity of breast cancer cells. 15 The SERCA pump is identified as an endoplasmic reticulum (EPR) protein. Its normal function is required for all cells and represents a potential therapeutic target for cancer therapy too.…”
mentioning
confidence: 99%
“…27 However, DIG is a well-characterized Na + /K + -ATPase inhibitor. 44 At relatively high concentrations (0.5-5 µM), DIG has the ability to inhibit the Na + /K + -ATPase pump, but at low concentrations (10-100 nM) may activate several transcriptional regulatory cascades via the Na + /K + -ATPase signalosome. 45 We recently found that DIG downregulates the expression of proteins involved in chemoresistance, survival, and stemness maintenance such as MDR1, ABCG2, Bcl-2, pAKT, and key proteins of the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%